Synthesis and Acid Catalysed Condensation of 3-(1-Hydroxy-4-chlorobenzyl) -1-methylindole - Mardi Santoso; David StC Black (Jurnal Matematika & Sains, 2003)
3-(1-Hydroxy-4-chlorobenzyl)-1-methylindole (3) has been synthesised in three steps. The first step involved methylation of indole to give N-methylindole (4) in 87% yield which on Vilsmeier-Haack formylation in the next step gave new ketone (5) in 67% yield. Sodium borohydride reduction of the new carbonyl compound (5) in the last step afforded the new indole alcohol (3) in 99% yield. Treatment of the secondary alcohol (3) with p-toluene sulfonic acid has been examined which afford di-(1-methylindol-3-yl)-(p-chlorophenyl)methane (7) in 71% yield.Â